Reevaluating approaches to cystic fibrosis pulmonary exacerbations. (6th July 2018) - Schechter, Michael S.
Abstract: Cystic Fibrosis (CF) lung disease is characterized by intermittent acute episodes of worsening signs, symptoms, and pulmonary function; these so‐called pulmonary exacerbations (PEx) appear to be important drivers of long‐term declines in lung function, quality of life, and life expectancy. Surveillance for development of PEx and their treatment is a fundamental component of chronic CF management, and the merits of novel CF therapies are often judged based on their ability to reduce the frequency of PEx. Given the central role that they play, it is surprising how poorly PEx are understood, how thin is the evidence base for their treatment and how often they are left unrecognized and untreated in clinical practice. This paper reviews what is known and what is unknown regarding the nature of PEx, and discusses the impact of missed recognition and treatment of these episodes as well as the apparent variation in practice across CF care centers. The arguments supporting a liberal, highly sensitive approach to the diagnosis of PEx are presented, as well as recommendation for how care programs can achieve consistency in their early recognition and treatment. A stepwise approach to personalized treatment supported by close follow‐up to ensure the successful resolution of all signs and symptoms will lead to the stabilization of patients' lung function and quality of life. Recommendations are made regarding important priorities for research into evidence‐based approaches to improving the care of PEx.